Implementasi Metode SAW (Simple Additive Weighting) pada Sistem Informasi Pendukung Keputusan Pembelian Rumah Layak Huni - Dedi Satria; Yeni Yanti (DPPM Universitas Pelita Bangsa, 2023)
A very important personal and financial decision for a person is buying a house. This decision can be influenced by many factors, such as location, physical condition of the property, price, and other factors that describe the needs and preferences of prospective buyers. the use of the SAW method in the context of information systems intended to help prospective home buyers make smarter decisions. the SAW (Simple Additive Weighting) method involves a number of stages, namely Determination of Criteria and Weights, Normalization of data, and Alternative Assessment, Ranking Alternatives. decision support system (SPK) based on SAW (Simple Additive Weighting) method using Criteria and weights consisting of criteria for Equipment, Location, Purchase Cost, and Model. From the housing data collected, it was found that Citra Indah Garden housing was at the top with a total value of 0.875, followed by Bumi Asri housing with a total value of 0.825, and ended with Taman Seri Indah housing with a total value of 0.75. Overall, Citra Indah Garden data is a livable housing choice according to predetermined criteria optimally. suggestions for the future of this research are to build a system using a more complex algorithm to get more optimal results and use more specific criteria.